Inventory of selected raptor, colonial, and sensitive bird species in the Athabasca oil sands area of Alberta ... - Ealey, D.; Beaver, R.; Munson, B.; Fyfe, R. (University of Alberta Library, 1980)
A three-year inventory of selected rare, endangered and sensitive bird species in the Athabasca Oil Sands area of northeastern Alberta was completed in the late summer of 1977. Aerial and ground surveys of the Alberta Oil Sands Environmental Research Program (AOSERP) study area and selected adjacent areas were conducted. Three major habitat types were investigated: the boreal mixed-wood forest of the Birch Mountains area; the jack pine sandplains south of Lake Athabasca and the Canadian Shield north of Lake Athabasca. Three major groups of birds were surveyed: raptors, colonial birds, and specified sensitive species. Locations of nest sites and colonies were noted and described. No attempt was made to determine the absolute abundance of each species in the AOSERP study area, as the aerial surveillance techniques employed do not justify such an estimation. The exception to this were two species whose total population in the AOSERP study area was restricted to very small areas and therefore could be readily ...